Pengembangan Mobile Mind Map dan Donkey Bridge Berbasis Android pada Konsep Sistem Gerak Manusia Sebagai Media Pembelajaran Kelas XI SMA/MA - Iksan, Iksan; Rahman KN, Aditya; Rifqiawati, Ika (Jurnal Pendidikan Indonesia, 2022)
The purpose of this research is to develop android-based learning media in the form of mind maps and donkey bridges on the material of the human movement system. This media is named Mobile Mind Maps and Donkey Bridge (M3DB). The method used in this research is research and development method. The media was tested by learning media experts and learning material experts. The score obtained from learning media experts is 88% while the score from learning materials experts is 90%, both of which fall into the very feasible category. The student response test was conducted at MA Al-Khairiyah Rancaranji with a total of 17 students. The results of the student response test showed that the M3DB learning media was included in the appropriate category (79%). The assessment category means that the M3DB learning media is worthy of being used as a learning medium in schools.